Bodyweight concerns: Examination of the psychometric properties of weight concerns scale in samples of Turkish athletes and university students - Baykose, Nazmi; Koruc, Ziya (Progress in Nutrition, 2021)
Study Objectives: Bodyweight concerns are common among people with eating disorders. This structure, which is in the common field of exercise psychology and nutrition, can be evaluated using self-report-type measurement tools. The Weight Concerns Scale (WCS) is often used to assess bodyweight concerns. To evaluate the psychometric characteristics of WCS in the sample of Turkish female university students and athletes; this study aims to adapt the scale of bodyweight concerns in Turkish culture. Methods: Confirmatory factor analysis was conducted for the research. Factorial, convergent and predictive validity and reliability were evaluated. Also, within the scope of the reliability analysis, the Cronbach's alpha internal consistency value was calculated. The invariance between samples of university students and athletes was tested by multi-group analysis. 446 female students and 398 female athletes voluntarily participated in the study. The psychometric properties of the WCS were sufficient for Turkish university students and athletes. WCS intergroup invariance was verified. Results: The psychometric properties of the WCS were sufficient for Turkish university students and athletes. WCS intergroup invariance was verified. Conclusion: It was determined that the Turkish form of the WCS can be used in the sample of Turkish students and athletes. WCS intergroup invariance was verified. In other words, the results show that it is an instrument that is simple to fill, requires minimum practice time, and can evaluate bodyweight concerns related to body image for Turkish university students and athletes.